(untitled) (Ustozlar uchun, 2025)
This paper provides a comparative analysis of the education systems of Canada and Uzbekistan, examining their structures, teaching and learning approaches, accessibility and equity policies, and teacher training models. Using a qualitative comparative method, the study highlights both shared goals and major differences in organization, pedagogy, and policy development. Findings indicate that Canada benefits from a highly decentralized, inclusive, and student-centered framework, while Uzbekistan has recently undertaken significant reforms aimed at modernization, digitalization, and improved teacher preparation. The comparison suggests mutual opportunities for growth and cross-cultural learning. Overall, this paper contributes to understanding how varying educational contexts shape national learning outcomes and long-term development.